Reconstructions before rifting and drifting reveal the geological connections between Antarctica and its conjugates in Gondwanaland - Veevers, J. J. (Earth-Science Reviews, 2012)
The initial (200-175 Ma) breakup of Pangea was marked by the emplacement of the Large Igneous Provinces (LIPS) of Karoo-Ferrar-SE Australia (KFS) in the back-arc of Panthalassan subduction and by the Central Atlantic Magmatic Province (CAMP) between Africa and the Americas. Seafloor spreading 190-180 Ma (Stage 1) about the CAMP split Pangea into northern (Laurasia) and southern (Gondwanaland) parts. Subsequent stages at 167 Ma (2), 147 Ma (3), 130 Ma (4), 118 Ma (5), and 83 Ma (6) split conjugate Africa, South America, India, Australia, and Zealandia from Antarctica. Here I review the reconstruction of Antarctica in Gondwanaland. First, seafloor spreading is unwound to re-unite the continent-ocean boundaries (COBs), then the extended (rifted) crust about the suture is restored to its original thickness. A comprehensive review of the U-Pb zircon geochronology of the reconstructed margins of Antarctica and its conjugates shows that certain coeval structures are aligned across the suture. Cross structures of high-order spatial continuity and age correlation are the Lambert-Mahanadi Rift, Pranhita-Godavari-Robert Glacier trend, Gawler-Adelie Craton, and western part of the Gondwanide Fold Belt Cross structures of high-order age correlation but low structural continuity or alignment are, from Africa to Antarctica, the East African-Antarctic Orogen, the Natal and Maud Belts, the Umkondo Group-Ritscherflya Supergroup and LIP, and the Kalahari-Grunehogna Craton; from Antarctica to Zealandia, the Ross-Western and Amundsen-Eastern Provinces; and from Africa through Antarctica to Australia the KFS LIP. (C) 2011 Elsevier B.V. All rights reserved.